ANALISIS SEMIOTIKA DAN NILAI KEBUDAYAAN MINANGKABAU DALAM FILM TENGGELAMNYA KAPAL VAN DER WICJK - Hidayat , Muhamad Mamduh (JURNAL SAHID DA'WATII, 2022)
Film is a form of mass communication that depends on the information it conveys and has the power to influence and shape the attitudes of its viewers. This research, which falls into the category of descriptive qualitative research, explores how Minangkabau cultural values are represented in the film "Tenggelamnya Kapal Van Der Wijck." The study uses Roland Barthes' semiotic analysis model, which includes two levels of meaning: connotation and denotation, as well as myth. The findings indicate that the film represents various aspects such as materialistic traits, the Minangkabau flag, Minangkabau traditional houses, traditional clothing, the washing of the groom's feet during Minangkabau traditional weddings, handshaking, deliberation, eating, and proverbs in the film "Tenggelamnya Kapal Van Der Wijck" with heartfelt sincerity.